Citizens' Solidarity in Europe: Civic Engagement and Public Discourse in Times of Crisis - Lahusen, Christian (Edward Elgar Publishing, 2020)
Citizens' Solidarity in Europe systematically dissects the manifestations of solidarity buried beneath the official policies and measures of public authority in Europe.   This critical book provides a comparative analysis of eight European countries, illustrating the scale of support for cross-national solidarity from both individuals and civic organizations. Contributors offer comprehensive and original data, analysing opinion polls, organizational fields and media content, to unpack the thoughts, opinions and attitudes of civil society. Chapters highlight the detrimental factors that tend to inhibit or annihilate solidarity, and those that are beneficial for the nurturing of solidarity.   Offering innovative ideas and fresh data, this book will be crucial reading for researchers and students of sociology and political science, particularly those focused on European and comparative studies. Journalists, NGOs, public authorities and politicians will also benefit from its unique insight into public opinion. Contributors include: S. Baglioni, V.K. Brändle, M. Cinalli, O. Eisele, V. Federico, M. Grasso, M. Kousis, C. Lahusen, A. Loukakis, T. Montgomery, M. Paschou, H.-J. Trenz